2020
DOI: 10.1109/access.2020.3020310
|View full text |Cite
|
Sign up to set email alerts
|

An Energy Proficient Load Balancing Routing Scheme for Wireless Sensor Networks to Maximize Their Lifespan in an Operational Environment

Abstract: Owing to the limited resources of sensor nodes, we propose an efficient hybrid routing scheme using a dynamic cluster-based static routing protocol (DCBSRP), leveraging the ad hoc on-demand distance vector (AODV) routing protocol and low-energy adaptive clustering hierarchy (LEACH) protocol. In the proposed scheme, the cluster head (CH) nodes are formed dynamically for a fixed interval, whereas static routing is applied in the designated clusters by utilizing the AODV routing protocol. The static routing condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 50 publications
0
40
0
Order By: Relevance
“…e hard threshold broadcasted by the CH to the respective cluster members is the attribute value above which the node is permitted to transmit the data to the CH. Once two-thirds of the nodes are dead and the residual energy of the remaining nodes is insufficient for clustering, the nodes use the greedy approach to form a chain-like multihop routing until the BS is reached [32][33][34][35][36][37][38][39][40][41][42].…”
Section: Operation Of the Optimal-cbr Algorithmmentioning
confidence: 99%
“…e hard threshold broadcasted by the CH to the respective cluster members is the attribute value above which the node is permitted to transmit the data to the CH. Once two-thirds of the nodes are dead and the residual energy of the remaining nodes is insufficient for clustering, the nodes use the greedy approach to form a chain-like multihop routing until the BS is reached [32][33][34][35][36][37][38][39][40][41][42].…”
Section: Operation Of the Optimal-cbr Algorithmmentioning
confidence: 99%
“…Load balancing technique is an important aspect to maximize the network lifetime of the sensors by minimizing energy consumption. According to an investigation by [62], authors use a new cluster formation scheme in the sensing field to manage the load balancing issue in the deployed area. The CH nodes in the proposed scheme are selected dynamically for a fixed interval.…”
Section: Wsn Communication Architecturementioning
confidence: 99%
“…This study is motivated by the discussions in [2], [4], [19], [21]- [23], [30]. In [30], it was shown that the DissR and DistrR protocols achieve short-term SLP protection and reduced network lifetime due to high energy consumption.…”
Section: A Motivationmentioning
confidence: 99%
“…Furthermore, it was shown that DissR incurs unbalanced energy distribution. The challenges of unbalanced energy distribution in WSNs were also highlighted in [2], [4]. Then, it was presented that when the challenge of unbalanced energy distribution is addressed, it can result in increased network lifetime and improved network reliability and feasibility.…”
Section: A Motivationmentioning
confidence: 99%